Why Pay More? Corporate Tax Avoidance through Transfer Pricing in OECD Countries - Eric J. Bartelsman; Roel Beetsma (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper presents evidence of profit shifting in response to differences in corporate tax rates for a large selection of OECD countries. In our estimates we control for the effects of tax rate changes on real activity. Our baseline estimates suggest that, on average, a unilateral increase in the corporate tax rate does not lead to an increase in corporate tax revenues owing to a more than offsetting decline in reported profits.
Keywords: 330; Profit shifting; transfer pricing; corporate tax rates; STAN database